Habitats under Contestation - Tali Hatuka (lo Squaderno, 2011)

(untitled)
To dwell, to inhabit, to reside, are all neutral verbs that portray the act of living in a place. And yet, the reality of contemporary dwelling is multifaceted. A dwelling is no longer a mere physical shelter (and maybe has never been) but rather a status symbol, an ideological choice, an opportunity, a territory, a barrier, a place constructed by and for humans and thus constantly being changed and contested. Nowadays a dwelling is nourished by geopolitical, cultural and economic changes such as increasing urban alienation, the increased power and influence of religious groups, the armies of city gangs, population growth, ownership, law etc.